Where the wild things are - Sendak, Maurice ([New York] : Harper Collins Publishers, 1991)
Max, a naughty little boy, sent to bed without his supper, sails to the land of the wild things where he becomes their king.
"Winner of the Caldecott Medal for the most distinguished picture book of the year"--Page [1].
Keywords: Monsters -- Juvenile fiction